Re-examining the law and economics of the business judgment rule: notes for its implementation in non-US jurisdictions. Issue 2 (3rd July 2018) - Gurrea-Martínez, Aurelio
ABSTRACT: The business judgment rule, as it has been traditionally understood, seems to be based on three underlying assumptions that make this rule economically desirable. First, directors are subject to a credible threat of being sued for a breach of the duty of care. Second, the primary role of the corporation is to maximise shareholder value. Third, shareholders want the directors to pursue those investment projects with the highest net present value regardless of their volatility. This article challenges these assumptions and argues that the business judgment rule might not be desirable in some jurisdictions outside the United States and even in many US corporations. Moreover, it points out that the implementation of the business judgment rule may actually create new, unintended costs. By re-examining the law and economics of the business judgment, this article draws conclusions about the most efficient way to implement the business judgment rule across jurisdictions.